Properties of sol-gel synthesized n-ZnO/n-GaN (0001) isotype heterojunction - Soylu, Murat; Yakuphanoğlu, Fahrettin (Elsevier Science Sa, 2014)
The electronic and optical properties of sol-gel synthesized n-ZnO/n-GaN (0001) isotype heterojunction were reported. By incorporating ZnO-GaN with the same wurtzite structure and the similar lattice constant, a heterojunction was fabricated. The junction properties were evaluated by measuring the electrical characteristics. The n-ZnO/n-GaN heterostructure exhibits a non-ideal I-V behavior with the ideality factor greater than unity that could be ascribed to the interfacial layer, interface states and series resistance. The forward turn on voltage is about 0.7 V and the reverse breakdown voltage is more than 2 V. The optical band gaps of the ZnO film and GaN using optical absorption method were found to be 3.272 eV and 3309 eV, respectively. The fundamental absorption edge in the film is formed by the direct allowed transitions. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Optical materials; Thin films; Sol-gel growth; Electrical properties